Pemanfaatan Web Service Sebagai Integrasi Data Pada Tata Laksana Laboratorium Komputer (Studi Kasus Lab.Komputer Lanjut Informatika STT-PLN) - Yessy Asri (Sekolah Tinggi Teknik - PLN, 2015)
Web service has an open service for the benefit of data integration and collaboration of information that can be accessed via the internet by various parties using technology owned by each user . Tata Laksana Computer Laboratory is based on client-server application that is implemented in a LAN network. With this application, the assistant and lecturers can convey information related to lab activities for students. The purpose of this paper is to design a mobile-based application program (android) and ASP.NET web service that is used as a link media between android application with a database. So that students can get information whenever they want.